Microtakaful - Syarah Syahira Mohd Yusoff; Muh Zul Hazmi Rapi; Siti Nursyawani Misman; Romzie Rosman; Rusni Hassan (Universiti Sains Islam Malaysia, 2025)
The Journal of Muamalat and Islamic Finance Research, Volume 22 Issue 1 Page (102–115)